A word-dedication to the famous theoreticians of the Conservatory - Jaghatspanyan Карине Азатовна (Musical Armenia, 2022)
In particular, the article refers to the brilliant specialists of YSC, Professors of the Theory Department Robert Atayan, Sergey Koptev and Rafael Stepanyan. Each of them stood out for their interesting teaching methods, unique thinking and methodological principles. The aim of the present article is to familiarize the young generations with those noteworthy methodological principles, forever strengthening bright memories of the abovementioned theoreticians.